Immunomodulatory Effects of Streptococcus suis Capsule Type on Human Dendritic Cell Responses, Phagocytosis and Intracellular Survival - Meijerink, Marjolein; Ferrando, Maria Laura; Lammers, Geraldine; Taverne, Nico; Smith, Hilde E.; Wells, Jerry M. (PLOS ONE, 2012)
Streptococcus suis is a major porcine pathogen of significant commercial importance worldwide and an emerging zoonotic pathogen of humans. Given the important sentinel role of mucosal dendritic cells and their importance in induction of T cell responses we investigated the effect of different S. suis serotype strains and an isogenic capsule mutant of serotype 2 on the maturation, activation and expression of IL-10, IL-12p70 and TNF-α in human monocyte-derived dendritic cells. Additionally, we compared phagocytosis levels and bacterial survival after internalization. The capsule of serotype 2, the most common serotype associated with infection in humans and pigs, was highly anti-phagocytic and modulated the IL-10/IL-12 and IL-10/TNF-α cytokine production in favor of a more anti-inflammatory profile compared to other serotypes. This may have consequences for the induction of effective immunity to S. suis serotype 2 in humans. A shielding effect of the capsule on innate Toll-like receptor signaling was also demonstrated. Furthermore, we showed that 24 h after phagocytosis, significant numbers of viable intracellular S. suis were still present intracellularly. This may contribute to the dissemination of S. suis in the body.